Lithium ion secondary battery

By regulating the hardness and silicon content of the insulating layer and negative electrode sheet in lithium-ion batteries, safety problems caused by battery burrs and the intensification of self-discharge are solved, and longer cycle life and higher safety performance are achieved.

CN119542510APending Publication Date: 2025-02-28ZHUHAI COSMX BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411706333.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-26
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

Lithium-ion batteries are prone to burrs in the position where the paste area and the empty foil area are connected on the electrode sheet, causing the separator to be pierced and causing safety problems. In addition, the negative electrode sheet with high silicon-based material content will intensify the battery's self-discharge, reducing service life and safety performance.

Method used

By adjusting the relationship between the Mohs hardness of the first inorganic particles in the insulating layer of the positive electrode sheet, the Mohs hardness of the silicon-based particles in the negative electrode sheet, and the mass content of silicon elements in the negative electrode active layer, the self-discharge problem of the battery is improved, and the cycle life and safety performance are improved.

Benefits of technology

It effectively reduces the occurrence of self-discharge of the battery, improves cycle life and safety performance, and ensures the stability and safety of the battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119542510A_ABST
    Figure CN119542510A_ABST
Patent Text Reader

Abstract

The invention relates to the field of batteries, in particular to a lithium ion secondary battery. Comprising a positive plate, a diaphragm and a negative plate which are stacked and wound, along the winding direction, a current collector of the positive plate is provided with a positive active layer and an insulating layer; the insulating layer partially covers the positive active layer and partially covers the current collector; the insulating layer comprises first inorganic particles with Mohs hardness of H1, and H1 is 5-8; the negative plate comprises a negative active layer containing silicon-based particles, the mass content c1 of the silicon element in the negative active layer is 4-45%, and the Mohs hardness H2 of the silicon-based particles is 8-10; h2 * c1 / H1 is more than or equal to 0.01 and less than or equal to 0.7. According to the lithium ion secondary battery, the relationship between the Mohs hardness of the first inorganic particles in the insulating layer on the positive plate and the Mohs hardness of the silicon-based particles in the negative plate is regulated and controlled, so that the self-discharge of the battery can be effectively improved, the cycle life of the battery is prolonged, and the safety performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of batteries, and in particular to a lithium-ion secondary battery. Background Art

[0002] Lithium-ion batteries are prone to burrs during the production process, especially at the junction of the paste area and the empty foil area on the pole piece. These burrs will pierce the diaphragm and cause a short circuit inside the battery, causing safety problems. For this reason, a safety coating can be applied to the places where burrs are prone to appear on the positive and negative poles of lithium-ion batteries to improve the safety problems caused by burrs piercing the diaphragm. At this time, if the silicon-based material content in the negative pole piece is high (for example, the mass content of silicon in the negative active coating is greater than or equal to 4%), it will cause the battery self-discharge to increase, thereby reducing the battery's service life and safety performance. Summary of the invention

[0003] The purpose of the present invention is to overcome the above problems existing in the prior art and provide a lithium ion secondary battery (hereinafter referred to as a battery). The battery of the present invention can effectively improve the self-discharge of the battery and improve the cycle life and safety performance of the battery by regulating the relationship between the Mohs hardness of the first inorganic particles in the insulating layer on the positive electrode sheet, the Mohs hardness of the silicon-based particles in the negative electrode sheet, and the mass content of the silicon element in the negative electrode active layer.

[0004] In the related art, an insulating layer is applied at the junction of the paste-coated area and the empty foil area of ​​the positive electrode to improve the problem caused by burrs piercing the diaphragm. However, if the content of silicon-based particles in the negative electrode is relatively high (for example, the mass content of silicon in the negative electrode active layer is greater than or equal to 4%), the self-discharge of the battery will be significantly aggravated. After a lot of research, the inventors of the present invention found that the reason for the above problems is that due to the large hardness of the silicon-based particles and the inorganic particles in the insulating layer, the silicon-based particles located at the position corresponding to the insulating layer of the positive electrode on the negative electrode are easily squeezed by the inorganic particles. At this time, the silicon-based particles with greater hardness will pierce the diaphragm, resulting in aggravated self-discharge of the battery. Based on the above findings, the inventors of the present invention have conducted a large number of targeted studies and proposed the following solutions:

[0005] The present invention provides a lithium ion secondary battery, comprising a positive electrode sheet, a separator and a negative electrode sheet which are stacked and wound; along the winding direction of the lithium ion secondary battery, a positive electrode active layer and an insulating layer are provided on a current collector of the positive electrode sheet; the insulating layer partially covers the positive electrode active layer and partially covers the current collector; the insulating layer comprises first inorganic particles, the Mohs hardness of the first inorganic particles is H1, and H1 is 5-8; the negative electrode sheet comprises a negative electrode active layer, the negative electrode active layer comprises silicon-based particles, the mass content of silicon element in the negative electrode active layer is c1, c1 is 4%-45%, the Mohs hardness of the silicon-based particles is H2, and H2 is 8-10; H1, H2 and c1 satisfy: 0.01≤H2×c1 / H1≤0.7.

[0006] By regulating the Mohs hardness of the first inorganic particles in the insulating layer, the mass content of silicon in the negative electrode active layer, and the Mohs hardness of the silicon-based particles, the occurrence of battery self-discharge can be effectively improved, thereby improving the cycle life and safety performance of the battery. This is because the silicon-based particles located at the position corresponding to the positive electrode insulating layer on the negative electrode sheet are easily squeezed by the first inorganic particles in the insulating layer. Therefore, the hardness of the silicon-based particles and the hardness of the first inorganic particles need to be regulated.

[0007] Since the silicon-based particles will expand and shrink in volume during the battery charge and discharge cycle, when the Mohs hardness of the first inorganic particles is relatively small (for example, less than 5), the inorganic particles with too small hardness cannot resist the extrusion from the silicon-based particles, which will cause imbalance inside the battery, thereby causing battery deformation. When the Mohs hardness of the first inorganic particles is relatively large (for example, greater than 8), the first inorganic particles may pierce the diaphragm due to their own excessive hardness, resulting in a short circuit. In addition, when the Mohs hardness of the silicon-based particles is relatively small (for example, less than 8), at this time, since they themselves will expand and shrink in volume during the battery charge and discharge cycle, if the hardness is insufficient, the negative electrode sheet structure will be unstable, which is not conducive to the battery cycle; and when the Mohs hardness of the silicon-based particles is relatively large (for example, greater than 10), at this time, the first inorganic particles in the protective layer are not enough to resist the extrusion of the silicon-based particles, which will not only cause the diaphragm to be pierced, but also cause the battery to deform.

[0008] However, if the Mohs hardness of the two is simply adjusted, the improvement of battery self-discharge is limited. The reason is that the mass content of silicon-based particles in the negative electrode active layer directly affects the squeezing effect of silicon-based particles on the first inorganic particles in the insulating layer. When the content is low, even if the Mohs hardness of silicon-based particles is large, the destructive effect on the diaphragm is not so obvious; but when the content of silicon-based particles is high, even by controlling the Mohs hardness of silicon-based particles and the Mohs hardness of the first inorganic particles, it is difficult to improve the squeezing effect of silicon-based particles on the first inorganic particles. Therefore, when the Mohs hardness of the first inorganic particles, the mass content of silicon in the negative electrode active layer, and the Mohs hardness of the silicon-based particles meet a specific relationship, the hardness of the first inorganic particles and the hardness of the silicon-based particles can reach a balance. Within this balance range, the insulating layer can well resist and buffer the squeezing from the silicon-based particles, effectively reducing the risk of self-discharge of the battery.

[0009] Through the above technical solution, the present invention has at least the following advantages compared with the prior art: the lithium ion secondary battery of the present invention can effectively reduce the occurrence of self-discharge, and improve the cycle life and safety performance.

[0010] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] Figure 1 FIG. 1 is a schematic diagram of a positive electrode sheet in an embodiment of the present invention; wherein, Figure 1 (a) is a top view, Figure 1 (b) is a side view.

[0012] Figure 2 Shown is a partial structural schematic diagram (cross-sectional view) of a lithium-ion secondary battery in an example of the present invention.

[0013] Figure 3 Shown is a schematic diagram of a partial structure of a battery in an example of the present invention.

[0014] Figure 4 FIG. 1 is a schematic diagram of the structure of a diaphragm in an example of the present invention; wherein, Figure 4 (a) and Figure 4 (b) The middle rubber layer is set on one side. Figure 4 (c) and Figure 4 (d) Set on both sides of the middle rubber layer. DETAILED DESCRIPTION

[0015] The specific embodiments of the present invention are described in detail below. It should be understood that the specific embodiments described herein are only used to illustrate and explain the present invention, and are not used to limit the present invention.

[0016] The present invention provides a lithium-ion secondary battery, which may include a positive electrode sheet, a separator and a negative electrode sheet stacked and wound. Along the winding direction of the lithium-ion secondary battery, the current collector of the positive electrode sheet has a positive electrode active layer and an insulating layer; the insulating layer partially covers the positive electrode active layer and partially covers the current collector. Figure 1 FIG. 1 is a schematic diagram of a positive electrode sheet in an embodiment of the present invention, wherein Figure 1 (a) is a top view, Figure 1 (b) is a side view. It can be seen from the figure that along the winding direction of the battery, the current collector 1-3 of the positive electrode sheet has a positive electrode active layer 1-1 and an insulating layer 1-2; the insulating layer 1-2 partially covers the positive electrode active layer 1-1 and partially covers the current collector 1-3, wherein: Figure 1 (a) and Figure 1 (b) shows an example where the insulating layer 1-2 is located at the tail end of the winding, and the insulating layer 1-2 can also be located at the head end of the winding; Figure 1 (b) shows an example in which the positive electrode active layer 1-1 and the insulating layer 1-2 are arranged on one side. The positive electrode active layer 1-1 and the insulating layer 1-2 may also be located on both sides of the current collector 1-3.

[0017] In the present invention, the insulating layer may include first inorganic particles, and the Mohs hardness of the first inorganic particles is H1, and H1 may be 5-8, for example, 5, 6, 7 or 8.

[0018] In the present invention, the negative electrode sheet may include a negative electrode active layer. The negative electrode active layer may include silicon-based particles. The mass content of silicon in the negative electrode active layer is c1, and c1 may be 4%-45%, for example, 4%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or 45%. The Mohs hardness of the silicon-based particles is H2, and H2 may be 8-10, for example, 8, 9 or 10.

[0019] In the present invention, H1, H2 and c1 satisfy: 0.01≤H2×c1 / H1≤0.7, for example, 0.01, 0.05, 0.1, 0.2, 0.3, 0.4, 0.5, 0.6 or 0.7.

[0020] In one example, 0.15≤H2×c1 / H1≤0.3.

[0021] In one example, 0.16≤H2×c1 / H1≤0.25.

[0022] In the present invention, the Mohs hardness H1 of the first inorganic particles and the Mohs hardness H2 of the silicon-based particles can be measured by conventional methods in the art, as follows:

[0023] (1) taking first inorganic particles or silicon-based particles as samples (ensuring that the sample surface is flat, if it is not flat, grinding or cutting can be used);

[0024] (2) Use a diamond pen with a grade of 1-10 to test the hardness of the sample;

[0025] (3) Fix the sample on a plane, and from the edge of the sample, move the selected diamond pen perpendicular to the sample surface and scratch the surface of the material with a slight force;

[0026] (4) Observe whether there are scratches on the sample surface, as well as the depth and length of the scratches. Then use a diamond pen with a higher hardness level to repeat the above test and observe the scratches. Repeat this process until you find the level of diamond pen that cannot produce scratches on the sample. This can be used to determine the Mohs hardness of the sample.

[0027] In the present invention, the mass content c1 of silicon in the negative electrode active layer can be measured by conventional methods in the art, such as scanning electron microscope-energy dispersive spectrometry (SEM-EDS).

[0028] In one example, c1 is 8%-25%.

[0029] The mass content of silicon in the negative electrode active layer not only has a significant impact on the self-discharge of the battery, but also affects the overall energy density and cycle stability of the battery. Under the premise that H2×c1 / H1 satisfies a specific relationship, by further adjusting c1, the battery can ensure a small self-discharge while taking into account both energy density and cycle stability.

[0030] In the present invention, the negative electrode active layer may further include carbon-based particles. The Mohs hardness of the carbon-based particles is H3, and H3 may be 1-3, such as 1, 2 or 3.

[0031] In the present invention, H2, H3 and c1 may satisfy: 0.02≤H2×c1 / H3≤4.5, for example, 0.02, 0.05, 0.1, 0.2, 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4 or 4.5.

[0032] In one example, 0.4≤H2×c1 / H3≤1.5.

[0033] In one example, 0.5≤H2×c1 / H3≤1.2.

[0034] When H2, H3 and c1 satisfy a specific relationship, it can effectively prevent the overly hard silicon-based particles from squeezing the carbon-based particles, reducing the risk of carbon-based particles being broken due to squeezing, thereby effectively avoiding the problems of battery capacity attenuation and analysis caused by the deactivation of carbon-based materials.

[0035] In the present invention, the separator may be located between the positive electrode sheet and the negative electrode sheet. Along the winding direction of the lithium-ion secondary battery, the separator may include a first portion and a second portion; the area where the separator contacts the insulating layer is located in the first portion. The adhesion between the separator located in the first portion and the negative electrode sheet may be 10N / m-20N / m, for example, 10N / m, 11N / m, 12N / m, 13N / m, 14N / m, 15N / m, 16N / m, 17N / m, 18N / m, 19N / m or 20N / m.

[0036] In one example, the adhesion between the separator located in the first portion and the negative electrode sheet is 13 N / m-19 N / m.

[0037] The battery includes a positive electrode sheet, a negative electrode sheet and a separator, wherein the separator is located between the positive electrode sheet and the negative electrode sheet to play a role of isolation. Therefore, one side of the separator is arranged in contact with the positive electrode sheet, and the other side of the separator is arranged in contact with the negative electrode sheet. Since the insulating layer contains the first inorganic particles, and the first inorganic particles have a relatively hard hardness. Therefore, the squeezing effect of the insulating layer on the separator is stronger than the squeezing effect of the positive electrode active layer on the separator. In addition, since the present invention regulates the relationship between the Mohs hardness of the first inorganic particles and the silicon-based particles and the mass content of the silicon element in the negative electrode active layer, the binder located in the insulating layer migrates through the separator to the negative electrode active layer at the corresponding position, thereby improving the bonding force between the separator located in the first part and the negative electrode sheet.

[0038] When the adhesion between the diaphragm located in the first part and the negative electrode sheet is within a specific range, it can not only improve the interface adhesion and enhance the overall structural stability of the battery, but also effectively inhibit the growth of lithium dendrites to prevent them from piercing the diaphragm and causing a short circuit.

[0039] In the present invention, the bonding strength between the diaphragm located in the first part and the negative electrode sheet can be tested by conventional methods in the art. For example, the negative electrode sheet bonded to the diaphragm located in the first part is cut into sheets with a width of 20 mm and a length of 100 mm, and a peeling force testing device is used to test the maximum force used to separate the diaphragm and the negative electrode sheet, which is the bonding strength.

[0040] In the present invention, the area where the diaphragm contacts the positive electrode active layer is located in the second part, and the adhesion between the diaphragm located in the second part and the negative electrode sheet can be 6N / m-15N / m, for example, 6N / m, 7N / m, 8N / m, 9N / m, 10N / m, 11N / m, 12N / m, 13N / m, 14N / m or 15N / m.

[0041] In one example, the adhesion between the separator located at the second portion and the negative electrode sheet is 8 N / m-12 N / m.

[0042] In the present invention, the adhesive force between the separator located in the first portion and the negative electrode sheet is greater than the adhesive force between the separator located in the second portion and the negative electrode sheet.

[0043] like Figure 2 The figure shows a schematic diagram (cross-sectional view) of the partial structure of a lithium-ion secondary battery in an example of the present invention. It can be seen from the figure that the lithium-ion secondary battery includes a positive electrode sheet 1, a separator 2 and a negative electrode sheet 3. The separator 2 is located between the positive electrode sheet 1 and the negative electrode sheet 3. The positive electrode sheet 1 includes a current collector 1-3 and a positive electrode active layer 1-1 and an insulating layer 1-2 located on one side surface of the current collector 1-3, and the insulating layer 1-2 partially covers the positive electrode active layer 1-1 and partially covers the current collector 1-3. Along the winding direction of the battery, the separator 2 includes a first part 2-1 and a second part 2-2; the area where the separator 2 contacts the insulating layer 1-2 is located in the first part 2-1, and the area where the separator 2 contacts the positive electrode active layer 1-1 is located in the second part 2-2. The bonding strength between the diaphragm 2 and the negative electrode sheet 3 located in the first part 2-1 is: the bonding strength between the diaphragm on the side adjacent to the negative electrode sheet 3 and located within the range of the first part 2-1 and the negative electrode sheet 3; the bonding strength between the diaphragm and the negative electrode sheet located in the second part is similar and will not be repeated here.

[0044] In the present invention, after 10 cycles at a voltage of 4.55 V or less, the elongation of the current collector of the positive electrode sheet in the first direction may be ≤1.5%, for example, 1.5%, 1.4%, 1.3%, 1.2%, 1.1%, 1%, 0.9%, 0.8%, 0.7%, 0.6%, 0.5%, 0.4%, 0.3%, 0.2%, 0.1%, 0.09%, 0.08%, 0.07%, 0.06%, 0.05%, 0.04%, 0.03%, 0.02% or 0.01%.

[0045] In one example, after the battery is cycled for 10 weeks at a voltage of 4.55 V or less, the elongation of the current collector of the positive electrode sheet in the first direction is 0.02%-0.8%.

[0046] In the present invention, the first direction refers to the extension direction of the positive electrode tab, and is also the width direction of the positive electrode sheet.

[0047] During the battery cycle, the negative electrode sheet expands in the length, width and thickness directions of the battery. The extension of the negative electrode sheet in the width direction will simultaneously drive the diaphragm to extend in this direction, and the extension of the diaphragm will drive the extension of the positive electrode sheet. At this time, the distance between the top angle of the battery cell (such as the top angle at the arc of the winding core) and the inner top angle of the packaging film (such as the aluminum-plastic film) will be reduced. The sharp edge of the positive electrode sheet will pierce the top angle of the packaging film, causing the battery cell to break at the corner, causing battery safety risks. An insulating layer is provided at the position where the positive electrode sheet paste area and the empty foil area meet, and the Mohs hardness of the first inorganic particles, the Mohs hardness of the silicon-based particles and the mass content of silicon in the negative electrode active layer are regulated, which can effectively inhibit the extension of the current collector of the positive electrode sheet in the width direction of the positive electrode sheet (i.e., the first direction, i.e., the extension direction of the positive electrode ear). This is because when the Mohs hardness of the first inorganic particles reaches a balance with the Mohs hardness of the silicon-based particles in the negative electrode active layer, the first inorganic particles can effectively resist and buffer the extrusion of the silicon-based particles, thereby delaying the extension of the current collector of the positive electrode sheet. When the extension rate is too large (for example, greater than 1.5%), the distance between the top corner of the battery cell and the top corner inside the packaging film decreases. At this time, the sharp edge of the positive electrode sheet will pierce the top corner of the packaging film, causing the battery cell to break at the corner, causing battery safety risks.

[0048] In the present invention, after the battery is cycled for 10 weeks at a voltage of 4.55 V or less, the elongation of the current collector of the positive electrode sheet in the first direction can be tested by conventional methods in the art, for example, a fresh battery is taken to measure the length A of the current collector of the positive electrode sheet in the first direction, and a battery is taken at a voltage of 4.55 V or less and has been cycled for 10 weeks to measure the length B of the current collector of the positive electrode sheet in the first direction, and then the elongation is obtained according to the formula: (B / A-1)×100%.

[0049] In the present invention, the silicon-based particles may include at least one of elemental silicon, silicon carbon, silicon oxygen, silicon nitrogen and silicon alloys. The silicon carbon is a material including elemental silicon and elemental carbon, such as silicon carbide; another example is a material formed by silicon or partially oxidized silicon filling (including partial filling or complete filling) in the pores of porous amorphous carbon or porous crystalline carbon. The silicon oxygen is a material including elemental silicon and elemental oxygen, such as silicon oxide. The silicon nitrogen is a material including elemental silicon and elemental nitrogen, such as silicon nitride. The carbon-based particles may include at least one of artificial graphite, natural graphite, mesophase carbon microspheres, soft carbon and hard carbon.

[0050] In the present invention, the first inorganic particles may include at least one of magnesium oxide, magnesium hydroxide, aluminum oxide, tungsten oxide, titanium oxide, silicon dioxide, and boehmite.

[0051] In one example, the first inorganic particles include alumina and / or boehmite.

[0052] In the present invention, the insulating layer may further include a first binder. The first binder may include at least one of polyvinylidene fluoride (PVDF), vinylidene fluoride-hexafluoropropylene copolymer (PVDF-HFP), styrene-butadiene rubber (SBR), polymethyl methacrylate (PMMA), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), sodium carboxymethyl cellulose (CMC-Na), lithium carboxymethyl cellulose (CMC-Li) and polyimide (PI).

[0053] In the present invention, the separator may include a substrate layer and a ceramic layer located on at least one side of the substrate layer, and the ceramic layer at least faces the positive electrode sheet. Figure 3 The figure shows a partial structural schematic diagram of a battery in an example of the present invention. It can be seen from the figure that the battery includes a positive electrode sheet 1, a separator 2 and a negative electrode sheet 3. The separator 2 includes a substrate layer 21 and a ceramic layer 22 located on one side of the substrate layer 21, and the ceramic layer 22 faces the positive electrode sheet 1. The ceramic layer may include second inorganic particles. The median particle size of the first inorganic particles is a first Dv50, and the median particle size of the second inorganic particles is a second Dv50.

[0054] In the present invention, the second Dv50 / the first Dv50 can be 0.25-10 (for example, 0.25, 0.3, 0.4, 0.5, 0.6, 0.7, 0.8, 0.9, 1.1, 2, 3, 4, 5, 6, 7, 8, 9 or 10), and the second Dv50≠the first Dv50.

[0055] In one example, the second Dv50 / the first Dv50 is 0.25-4.

[0056] In one example, the second Dv50 / the first Dv50 is 0.25-3.

[0057] The inventors of the present invention have found that when the ratio of the median particle size of the first inorganic particles to the second inorganic particles is within a specific range, the risk of battery short circuit can be further reduced. This is because the first inorganic particles in the insulating layer disposed at the junction of the paste area and the empty foil area cannot completely cover burrs of all sizes. When the uncovered burrs come into contact with the ceramic layer on the diaphragm, since the hardness of the ceramic layer is larger than that of the active material layer, this part of the uncovered burrs will be flattened by the ceramic layer, but due to the presence of the extrusion force, the inorganic particles located at the junction of the paste area and the empty foil area will bulge, thereby piercing the diaphragm and causing self-discharge. When the ratio of the median particle size of the first inorganic particles to the second inorganic particles is within a specific range, burrs of various sizes can be well embedded in the insulating layer and the ceramic layer, which can effectively prevent the inorganic particles from piercing the diaphragm due to the extrusion force. In addition, by adjusting the ratio of the median particle size of the first inorganic particle to the second inorganic particle, it is more conducive to providing a rich pore structure to store electrolyte to reduce the risk of lithium precipitation. It is also conducive to reducing the thickness of the ceramic layer on the diaphragm to reduce the thickness of the battery, thereby increasing the volume energy density of the battery.

[0058] In the present invention, the first Dv50 may be 0.2 μm-5 μm, for example, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.5 μm, 2 μm, 3 μm, 4 μm or 5 μm.

[0059] In one example, the first Dv50 is 0.5 μm-2 μm.

[0060] In the present invention, the second Dv50 may be 0.2 μm-5 μm, for example, 0.2 μm, 0.3 μm, 0.4 μm, 0.5 μm, 0.6 μm, 0.7 μm, 0.8 μm, 0.9 μm, 1 μm, 1.5 μm, 2 μm, 3 μm, 4 μm or 5 μm.

[0061] In one example, the second Dv50 is 0.5 μm-2 μm.

[0062] In the present invention, the first Dv50 and the second Dv50 can be tested by conventional methods in the art, for example, by a laser particle size analyzer, specifically as follows: the insulating layer and the ceramic layer are scraped off by a blade, and subjected to grinding and other treatments to obtain first inorganic particles and second inorganic particles, respectively, and the obtained first inorganic particles and second inorganic particles are respectively sent to a laser particle size analyzer for detection.

[0063] In the present invention, the second inorganic particles may include at least one of magnesium oxide, magnesium hydroxide, aluminum oxide, tungsten oxide, titanium oxide, silicon dioxide, and boehmite.

[0064] In the present invention, the ceramic layer may further include a second binder. The second binder may include at least one of PVDF, PVDF-HFP, SBR, PMMA, PAA, CMC, CMC-Na, CMC-Li and PI.

[0065] In order to further improve the cycle stability of the battery, it is necessary to ensure the bonding ability between the insulating layer and the separator to prevent the battery from deforming and maintain the normal charge and discharge cycle of the battery. Therefore, it is necessary to limit the content of the binder in the insulating layer and the ceramic layer.

[0066] In the present invention, based on the total mass of the insulating layer, the content of the first adhesive can be 5%-30%, for example, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19%, 20%, 21%, 22%, 23%, 24%, 25%, 26%, 27%, 28%, 29% or 30%.

[0067] In one example, based on the total mass of the insulating layer, the content of the first binder is 8%-15%.

[0068] In the present invention, based on the total mass of the ceramic layer, the content of the second binder can be 1%-20%, for example, 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, 15%, 16%, 17%, 18%, 19% or 20%.

[0069] In one example, based on the total mass of the ceramic layer, the content of the second binder is 2%-10%.

[0070] In one example, a mass content of the first binder in the insulating layer is greater than a mass content of the second binder in the ceramic layer.

[0071] The inventors of the present invention have discovered that by adjusting the mass content of the first binder in the ceramic layer to be greater than the mass content of the second binder in the ceramic layer, the pore blocking problem of the diaphragm can be effectively improved while ensuring stable bonding between the positive electrode sheet and the diaphragm, which is beneficial to improving the lithium plating problem of the battery.

[0072] In the present invention, the thickness of the positive electrode active layer may be 30 μm-75 μm, for example, 30 μm, 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm or 75 μm.

[0073] In one example, the thickness of the positive electrode active layer is 35 μm-60 μm.

[0074] In the present invention, the thickness of the insulating layer may be 1 μm-15 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm.

[0075] In one example, the thickness of the insulating layer is 3 μm-12 μm.

[0076] In the present invention, the thickness of the positive electrode active layer refers to the thickness of the portion located on one side of the current collector and not covered by the insulating layer. The thickness of the insulating layer refers to the thickness of the portion located on one side of the current collector and covering the current collector.

[0077] In the present invention, in the winding direction of the lithium ion secondary battery, the size of the insulating layer portion covering the positive electrode active layer is d1, and the size of the insulating layer portion covering the current collector is d2. d1 and d2 satisfy d2 / d1 of 0.6-10, for example, 0.6, 0.67, 0.8, 0.85, 0.86, 1, 2, 3, 4, 5, 6, 7, 8, 9 or 10.

[0078] In one example, d2 / d1 is 0.85-5.

[0079] By adjusting d2 / d1, it can be ensured that the position where the paste-coated area and the empty foil area on the negative electrode sheet meet falls within the insulating layer, so as to reduce the risk of short circuit of the battery when the burrs at the position where the paste-coated area and the empty foil area of ​​the negative electrode sheet meet pierce the diaphragm.

[0080] In the present invention, d1 may be 2 mm-15 mm, for example, 2 mm, 3 mm, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 11 mm, 12 mm, 13 mm, 14 mm or 15 mm.

[0081] In one example, d1 is 3 mm-7 mm.

[0082] In the present invention, d2 may be 4 mm-30 mm, for example, 4 mm, 5 mm, 6 mm, 7 mm, 8 mm, 9 mm, 10 mm, 15 mm, 20 mm, 25 mm or 30 mm.

[0083] In one example, d2 is 6 mm-15 mm.

[0084] In the present invention, the insulating layer covering the positive electrode active layer is partially embedded in the positive electrode active layer.

[0085] In one example, the first inorganic particles are embedded in the positive electrode active layer.

[0086] By further controlling the position of the first inorganic particles so that the first inorganic particles are embedded in the positive electrode active layer, the conductive network of the positive electrode active layer in this region can be disrupted, reducing its conductivity and increasing its impedance, which can further block the transport of lithium ions in the insulating layer, thereby preventing the occurrence of lithium plating.

[0087] In the present invention, the vertical distance from the first inorganic particles in the insulating layer covering the positive electrode active layer to the surface of the insulating layer can be 2 μm - 15 μm, such as 2 μm, 3 μm, 4 μm, 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm or 15 μm.

[0088] By regulating the vertical distance from the first inorganic particles in the insulating layer covering the positive electrode active layer to the surface of the insulating layer, it is possible to further prevent excessive burrs from piercing through the gaps of the first inorganic particles to the surface of the insulating layer, resulting in the occurrence of micro-short circuits. While ensuring low self-discharge of the battery, it does not increase the ineffective thickness of the positive electrode sheet, which is beneficial to reducing the battery thickness to improve the volumetric energy density.

[0089] In one example, the vertical distance from the first inorganic particles in the insulating layer covering the positive electrode active layer to the surface of the insulating layer is 3 μm - 8 μm.

[0090] In the present invention, the vertical distance from the first inorganic particles to the surface of the insulating layer can be obtained by testing with conventional methods in the art. For example, using SEM, within the field of view, at least 10 first inorganic particles are randomly selected, and the minimum value of the vertical distance from the surface of each first inorganic particle to the surface of the insulating layer is measured, and the average value is taken.

[0091] In the present invention, the negative electrode active layer may include a negative electrode active material, and the negative electrode active material may include the silicon-based particles and the carbon-based particles.

[0092] In the present invention, the positive electrode sheet may further include a positive electrode active material, and the positive electrode active material may include a substance with the chemical formula Li a Ni b Co c Mn d M e O2, where 0.8 ≤ a ≤ 1.3, 0.8 ≤ b ≤ 0.98, 0.01 ≤ c ≤ 0.2, 0.005 ≤ d ≤ 0.14, 0 < e ≤ 0.08, and M may include at least one of Al, Zr, B, Y, Sr, W, Ti, Mg, La, Fe, and Nb.

[0093] When 0.8≤b≤0.98 in the positive electrode active material, the demand for electrolyte will increase. When the electrolyte is lacking, it is easy to cause side reactions, which will further lead to the consumption of electrolyte, causing black spots and lithium precipitation. The junction of the paste area and the empty foil area on the positive electrode sheet is more likely to cause lithium precipitation and black spots due to lack of electrolyte. At this time, the insulating layer can increase the residual liquid amount at this location, thereby improving the lithium precipitation and black spot problems caused by lack of electrolyte.

[0094] In the present invention, the thickness of the ceramic layer may be 1 μm-5 μm, for example, 1 μm, 2 μm, 3 μm, 4 μm or 5 μm.

[0095] In the present invention, the insulating layer may be located at the winding beginning and / or the winding end of the positive electrode sheet.

[0096] In the present invention, the positive electrode sheet, the separator and the negative electrode sheet are stacked and wound to form a winding core, and the insulating layer may be located at the winding head end and / or the winding tail end of the winding core.

[0097] In the present invention, in the winding direction of the lithium-ion secondary battery, the size of the ceramic layer exceeds the size of the positive electrode sheet.

[0098] In the present invention, the diaphragm further comprises a glue layer, and the glue layer may be located on the outermost surface of at least one side of the diaphragm. Figure 4 FIG. 1 is a schematic diagram of the structure of a diaphragm in an example of the present invention; wherein, Figure 4 (a) and Figure 4 (b) The middle rubber layer is set on one side. Figure 4 (c) and Figure 4 (d) The rubber layer is set on both sides. Figure 4 (a) The diaphragm includes a substrate layer 21, a ceramic layer 22 located on one side of the substrate layer 21, and a glue layer 23 located on the outer surface of the ceramic layer 22. Figure 4 (b) The diaphragm includes a substrate layer 21, a ceramic layer 22 located on both sides of the substrate layer 21, and a glue layer 23 located on the outer surface of one side of the diaphragm. Figure 4 (c) The diaphragm includes a substrate layer 21, a ceramic layer 22 located on one side of the substrate layer 21, and a glue layer 23 located on both sides of the outer surface of the diaphragm. Figure 4 (d) The middle diaphragm includes a substrate layer 21 , a ceramic layer 22 located on both side surfaces of the substrate layer 21 , and a glue layer 23 located on the outer surface of the ceramic layer 22 .

[0099] The adhesive layer may include a binder, and the binder may include at least one of PVDF, PVDF-HFP, SBR, PMMA, PAA, CMC, CMC-Na, CMC-Li, and PI.

[0100] In the present invention, the positive electrode active material layer may include the positive electrode active material, a positive electrode conductive agent and a positive electrode binder. The positive electrode conductive agent may include a conductive agent conventionally used in the art, for example, including at least one of conductive carbon black, acetylene black, Ketjen black, conductive graphite, conductive carbon fiber and carbon nanotubes (including at least one of single-walled carbon nanotubes and multi-walled carbon nanotubes). The positive electrode binder may include a binder conventionally used in the art, for example, including at least one of polyvinylidene fluoride, sodium carboxymethyl cellulose, styrene-butadiene rubber, polytetrafluoroethylene and polyethylene oxide.

[0101] In the present invention, based on the total mass of the positive electrode active material layer, the content of the positive electrode active material can be 80%-99.8% (for example, 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, 98%, 99% or 99.8%), the content of the positive electrode conductor can be 0.1%-10% (for example, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5% or 0.1%), and the content of the positive electrode binder can be 0.1%-10% (for example, 10%, 9%, 8%, 7%, 6%, 5%, 4%, 3%, 2%, 1%, 0.5% or 0.1%).

[0102] In the present invention, the battery may further include an electrolyte, which may include a negative electrode sheet and an electrolyte conventionally used in the art.

[0103] It should be noted that the numerical expressions such as "first" and "second" in the present invention are only used to distinguish different substances or usages, and do not represent the difference in order.

[0104] The present invention will be described in detail below by way of examples. The examples described in the present invention are only a part of the examples of the present invention, rather than all of the examples. Based on the examples in the present invention, all other examples obtained by ordinary technicians in the field without creative work are within the scope of protection of the present invention.

[0105] In the following examples, unless otherwise specified, all materials used were commercially available of analytical grade.

[0106] Example

[0107] The following examples are used to illustrate the lithium ion secondary battery of the present invention.

[0108] Example 1

[0109] Prepare the battery as follows:

[0110] (1) Preparation of positive electrode

[0111] The positive electrode active material (LiNi 0.9 Co 0.05 Mn 0.02 Mg 0.03 O2), PVDF and conductive carbon black are mixed in a mass ratio of 97.5:1.5:1, N-methylpyrrolidone (NMP) is added to prepare a positive electrode active material slurry (solid content is 60wt%), the above positive electrode active material slurry is evenly coated on the surface of aluminum foil, and dried (to obtain a positive electrode active layer); boehmite (Mohs hardness H1 is 7, the first Dv50 is 0.5μm) and PVDF are mixed in a mass ratio of 88:12, NMP is added to prepare an insulating layer slurry (solid content is 60wt%), the above insulating layer slurry is coated on the tail of the positive electrode active layer, dried, and compacted by a roller press to obtain a positive electrode sheet;

[0112] Among them, d1 is 3 mm, d2 is 15 mm, and d2 / d1 is 5; the thickness of the positive electrode active layer is 50 μm, and the thickness of the insulating layer is 8 μm; boehmite is embedded in the positive electrode active layer, and the vertical distance from the boehmite particles to the surface of the insulating layer is 3 μm.

[0113] (2) Preparation of negative electrode sheet

[0114] A negative electrode active material (artificial graphite and silicon carbon, the Mohs hardness H2 of silicon carbon is 9, and the Mohs hardness H3 of artificial graphite is 2), SBR and conductive carbon black are mixed in a mass ratio of 95:3:2 to form a uniform and stable mixture, deionized water is added to prepare a negative electrode active material slurry (solid content is 46wt%), and the above negative electrode active material slurry is evenly coated on both sides of a copper foil, and after drying and roller pressing, a negative electrode sheet is obtained;

[0115] The mass content c1 of silicon in the negative electrode active layer is 15%.

[0116] (3) Preparation of electrolyte

[0117] In a glove box filled with argon (H2O < 0.1 ppm, O2 < 0.1 ppm), ethylene carbonate, dimethyl carbonate and 1,2-propylene carbonate were mixed in a volume ratio of 1:1:1, 1 M lithium hexafluorophosphate was added, stirred evenly, and the electrolyte was obtained after passing the moisture and free acid tests.

[0118] (4) Preparation of diaphragm

[0119] Alumina (the second Dv50 is 1.5μm) and PVDF are mixed in a mass ratio of 94:6, and NMP is added to prepare a ceramic layer slurry (solid content is 60wt%), and the above ceramic layer slurry is applied to one side of the polyethylene film; PVDF is added to NMP to obtain a glue layer slurry (solid content is 60wt%), and the above glue layer slurry is applied to the outer surface of the ceramic layer and the other side of the polyethylene film, and dried to obtain a diaphragm, wherein the ceramic layer thickness is 3μm.

[0120] (5) Preparation of batteries

[0121] The positive electrode sheet prepared in step (1), the separator prepared in step (4) and the negative electrode sheet prepared in step (2) are wound to form a winding core, and the aluminum pole ear and the copper-plated nickel pole ear are welded after hot pressing; after liquid injection, the battery is formed, sorted, and OCV tested to obtain a battery, wherein the insulating layer is located at the winding tail end of the winding core, and in the winding direction, the size of the ceramic layer exceeds the size of the positive electrode sheet, and the ceramic layer of the separator faces the positive electrode sheet;

[0122] Among them, H2×c1 / H1 is 0.193;

[0123] H2×c1 / H3 is 0.675;

[0124] Second Dv50 / first Dv50 is 3.

[0125] Example 2

[0126] Prepare the battery as follows:

[0127] (1) Preparation of positive electrode

[0128] The positive electrode active material (LiNi 0.85 Co 0.1 Mn 0.02 Al 0.03 Aluminum oxide (Mohs hardness H1 is 5, the first Dv50 is 1 μm) and PVDF are mixed in a mass ratio of 92:8, NMP is added to make an insulating layer slurry (solid content is 60wt%), the insulating layer slurry is applied to the tail of the positive electrode active layer, dried, and compacted by a roller press to obtain a positive electrode sheet;

[0129] Among them, d1 is 7 mm, d2 is 6 mm, d2 / d1 is 0.86; the thickness of the positive electrode active layer is 50 μm, and the thickness of the insulating layer is 3 μm; alumina is embedded in the positive electrode active layer, and the vertical distance from the alumina particles to the surface of the insulating layer is 8 μm.

[0130] (2) Preparation of negative electrode sheet

[0131] A negative electrode active material (artificial graphite and silicon carbon, the Mohs hardness of silicon carbon is H2 8, and the Mohs hardness of artificial graphite is H3 1), SBR and conductive carbon black are mixed in a mass ratio of 95:3:2 to form a uniform and stable mixture, deionized water is added to prepare a negative electrode active material slurry (solid content is 46wt%), and the above negative electrode active material slurry is evenly coated on both sides of a copper foil, and after drying and roller pressing, a negative electrode sheet is obtained;

[0132] The mass content c1 of silicon in the negative electrode active layer is 15%.

[0133] (3) Preparation of electrolyte

[0134] In a glove box filled with argon (H2O < 0.1 ppm, O2 < 0.1 ppm), ethylene carbonate, dimethyl carbonate and 1,2-propylene carbonate were mixed in a volume ratio of 1:1:1, 1 M lithium hexafluorophosphate was added, stirred evenly, and the electrolyte was obtained after passing the moisture and free acid tests.

[0135] (4) Preparation of diaphragm

[0136] Boehmite (the second Dv50 is 2μm) and PVDF are mixed in a mass ratio of 98:2, and NMP is added to prepare a ceramic layer slurry (solid content is 60wt%), and the above ceramic layer slurry is applied to one surface of the polyethylene film; PVDF is added to NMP to obtain an adhesive layer slurry (solid content is 60wt%), and the above adhesive layer slurry is applied to the outer surface of the ceramic layer and the other surface of the polyethylene film, and dried to obtain a diaphragm, wherein the ceramic layer thickness is 1μm.

[0137] (5) Preparation of batteries

[0138] The positive electrode sheet prepared in step (1), the separator prepared in step (4) and the negative electrode sheet prepared in step (2) are wound to form a winding core, and the aluminum pole ear and the copper-plated nickel pole ear are welded after hot pressing; after liquid injection, the battery is formed, sorted, and OCV tested to obtain a battery, wherein the insulating layer is located at the winding tail end of the winding core, and in the winding direction, the size of the ceramic layer exceeds the size of the positive electrode sheet, and the ceramic layer of the separator faces the positive electrode sheet;

[0139] Among them, H2×c1 / H1 is 0.24;

[0140] H2×c1 / H3 is 1.2;

[0141] Second Dv50 / first Dv50 is 2.

[0142] Example 3

[0143] Prepare the battery as follows:

[0144] (1) Preparation of positive electrode

[0145] The positive electrode active material (LiNi 0.85 Co 0.1 Mn 0.02 Ti 0.03 O2), PVDF and conductive carbon black are mixed in a mass ratio of 97.5:1.5:1, N-methylpyrrolidone (NMP) is added to prepare a positive electrode active material slurry (solid content is 60wt%), the above positive electrode active material slurry is evenly coated on the surface of the aluminum foil, and dried (to obtain a positive electrode active layer); the first inorganic particles (alumina and boehmite are mixed in a mass ratio of 1:1, Mohs hardness H1 is 8, and the first Dv50 is 2μm) and PVDF are mixed in a mass ratio of 85:15, NMP is added to prepare an insulating layer slurry (solid content is 60wt%), the above insulating layer slurry is coated on the tail of the positive electrode active layer, dried, and compacted by a roller press to obtain a positive electrode sheet;

[0146] Among them, d1 is 5 mm, d2 is 10 mm, and d2 / d1 is 2; the thickness of the positive electrode active layer is 50 μm, and the thickness of the insulating layer is 12 μm; alumina and boehmite are embedded in the positive electrode active layer, and the vertical distance from the alumina particles and the boehmite particles to the surface of the insulating layer is 5 μm.

[0147] (2) Preparation of negative electrode sheet

[0148] A negative electrode active material (artificial graphite and silicon carbon, the Mohs hardness H2 of silicon carbon is 10, and the Mohs hardness H3 of artificial graphite is 3), SBR and conductive carbon black are mixed in a mass ratio of 95:3:2 to form a uniform and stable mixture, deionized water is added to prepare a negative electrode active material slurry (solid content is 46wt%), and the above negative electrode active material slurry is evenly coated on both sides of a copper foil, and after drying and roller pressing, a negative electrode sheet is obtained;

[0149] The mass content c1 of silicon in the negative electrode active layer is 15%.

[0150] (3) Preparation of electrolyte

[0151] In a glove box filled with argon (H2O < 0.1 ppm, O2 < 0.1 ppm), ethylene carbonate, dimethyl carbonate and 1,2-propylene carbonate were mixed in a volume ratio of 1:1:1, 1 M lithium hexafluorophosphate was added, stirred evenly, and the electrolyte was obtained after passing the moisture and free acid tests.

[0152] (4) Preparation of diaphragm

[0153] The second inorganic particles (alumina and boehmite are mixed in a mass ratio of 1:1, and the second Dv50 is 0.5μm) and PVDF are mixed in a mass ratio of 90:10, and NMP is added to prepare a ceramic layer slurry (solid content is 60wt%), and the above ceramic layer slurry is applied to one surface of the polyethylene film; PVDF is added to NMP to obtain a glue layer slurry (solid content is 60wt%), and the above glue layer slurry is applied to the outer surface of the ceramic layer and the other surface of the polyethylene film, and dried to obtain a diaphragm, wherein the ceramic layer thickness is 5μm.

[0154] (5) Preparation of batteries

[0155] The positive electrode sheet prepared in step (1), the separator prepared in step (4) and the negative electrode sheet prepared in step (2) are wound to form a winding core, and the aluminum pole ear and the copper-plated nickel pole ear are welded after hot pressing; after liquid injection, the battery is formed, sorted, and OCV tested to obtain a battery, wherein the insulating layer is located at the winding tail end of the winding core, and in the winding direction, the size of the ceramic layer exceeds the size of the positive electrode sheet, and the ceramic layer of the separator faces the positive electrode sheet;

[0156] Among them, H2×c1 / H1 is 0.188;

[0157] H2×c1 / H3 is 0.5;

[0158] The second Dv50 / first Dv50 is 0.25.

[0159] Example 4 Group

[0160] This group of embodiments is used to verify the impact of the change of "H2×c1 / H1".

[0161] This group of examples is carried out with reference to Example 2 and Example 3, except that the Mohs hardness H2 of silicon carbon is changed to adjust H2×c1 / H1, as follows:

[0162] Example 4a is carried out with reference to Example 2, except that:

[0163] H2 is 10, H3 is 3 (in order to reduce the impact caused by the change of "H2×c1 / H3", the Mohs hardness H3 of artificial graphite is also adjusted);

[0164] Among them, H2×c1 / H1 is 0.3; H2×c1 / H3 is 0.5;

[0165] Example 4b is carried out with reference to Example 3, except that:

[0166] H2 is 8, H3 is 1 (in order to reduce the impact caused by the change of "H2×c1 / H3", the Mohs hardness H3 of artificial graphite is also adjusted);

[0167] Among them, H2×c1 / H1 is 0.15; H2×c1 / H3 is 1.2.

[0168] Example 5 Group

[0169] This group of embodiments is used to verify the impact of the change of "H2×c1 / H3".

[0170] This group of examples is carried out with reference to Example 1, except that H2×c1 / H3 is adjusted by changing the Mohs hardness H2 of silicon carbon and the Mohs hardness H3 of artificial graphite, as follows:

[0171] Example 5a, H2 is 8, H3 is 3;

[0172] Among them, H2×c1 / H1 is 0.171; H2×c1 / H3 is 0.4;

[0173] Example 5b, H2 is 10, H3 is 1;

[0174] Among them, H2×c1 / H1 is 0.214; H2×c1 / H3 is 1.5;.

[0175] Example 6 Group

[0176] This group of examples is used to verify the influence of the change of "the mass content c1 of silicon element in the negative electrode active layer".

[0177] This group of examples is carried out with reference to Example 1, except that c1 is regulated by changing the mass ratio of artificial graphite and silicon carbon in the negative electrode active material, as follows:

[0178] Example 6a, c1 is 8%; H1 is 5, H2 is 10, H3 is 1; H2×c1 / H1 is 0.16; H2×c1 / H3 is 0.8;

[0179] Example 6b, c1 is 25%; H1 is 8, H2 is 8, H3 is 3; H2×c1 / H1 is 0.25; H2×c1 / H3 is 0.667;

[0180] Example 6c, c1 is 4%; H1 is 7, H2 is 8, H3 is 3; H2×c1 / H1 is 0.011; H2×c1 / H3 is 0.027;

[0181] In Example 6d, c1 is 45%; H1 is 7, H2 is 10, and H3 is 1; H2×c1 / H1 is 0.643; and H2×c1 / H3 is 4.5.

[0182] Example 7

[0183] Used to verify the impact of the change of "Second Dv50 / First Dv50".

[0184] The same procedure is carried out with reference to Example 1, except that the second Dv50 / first Dv50 is regulated by changing the second Dv50. Specifically, the second Dv50 is 2 μm, and the second Dv50 / first Dv50 is 4.

[0185] Example 8 Group

[0186] This group of examples is used to verify the influence of the change of "the mass content of the first inorganic particles in the insulating layer".

[0187] This group of examples is carried out with reference to Example 1, except that the mass content of the first inorganic particles in the insulating layer is changed, as follows:

[0188] In Example 8a, the mass ratio of boehmite to PVDF is 95:5; wherein the mass content of the first binder in the insulating layer is less than the mass content of the second binder in the ceramic layer;

[0189] In Example 8b, the mass ratio of boehmite to PVDF is 70:30.

[0190] Example 9 Group

[0191] This group of embodiments is used to verify the impact of changes in the "thickness of the insulating layer".

[0192] This group of embodiments is carried out with reference to Embodiment 1, except that the thickness of the insulating layer is changed, as follows:

[0193] In Example 9a, the thickness of the insulating layer is 1 μm;

[0194] In Example 9b, the thickness of the insulating layer is 15 μm.

[0195] Example 10 Group

[0196] This group of embodiments is used to verify the impact of the change of "d1".

[0197] This group of examples is carried out with reference to Example 1, except that d1 is changed, as follows:

[0198] Example 10a, d1 is 2 mm, d2 / d1 is 7.5;

[0199] In Example 10b, d1 is 15 mm and d2 / d1 is 1.

[0200] Example 11 Group

[0201] This group of embodiments is used to verify the impact of the change of "d2".

[0202] This group of examples is carried out with reference to Example 1, except that d2 is changed, as follows:

[0203] In Example 11a, d2 is 4 mm, and d2 / d1 is 1.3;

[0204] In embodiment 11b, d2 is 30 mm and d2 / d1 is 10.

[0205] Example 12 Group

[0206] This group of embodiments is used to verify the influence of the change of "the vertical distance from the first inorganic particle to the surface of the insulating layer".

[0207] This group of examples is carried out with reference to Example 1, except that different vertical distances from the first inorganic particles to the surface of the insulating layer are obtained by screening, as follows:

[0208] Example 12a, the vertical distance from the boehmite particles to the surface of the insulating layer is 15 μm;

[0209] In Example 12a, the vertical distance between the boehmite particles and the surface of the insulating layer is 2 μm.

[0210] Test Case I

[0211] (1) Adhesion test

[0212] The lithium-ion secondary battery prepared in the example was tested for adhesion between the separator and the negative electrode sheet in a specific area, and the results were rounded and recorded in Table 1.

[0213] (2) Current collector elongation test

[0214] The lithium ion secondary battery prepared in the example was cycled for 10 weeks at a voltage of 4.55 V, and the elongation of the current collector of the positive electrode sheet in the first direction was recorded in Table 1.

[0215] Table 1

[0216]

[0217]

[0218] Comparative Example 1

[0219] The same method is carried out as in Example 1, except that the negative electrode active materials are all artificial graphite.

[0220] Comparative Example 2

[0221] The method was carried out with reference to Example 1, except that the mass ratio of artificial graphite and silicon carbon in the negative electrode active material and the Mohs hardness H2 of silicon carbon were changed, specifically: c1 was 60%, H2 was 10; H2×c1 / H1 was 0.857.

[0222] Test Case II

[0223] (1) Short circuit rate test

[0224] The batteries prepared in the examples and comparative examples were tested for short circuit rate. The specific test method is as follows: Use a multimeter adjusted to the resistance position, and then connect the positive and negative electrodes of the battery to the test leads respectively. If the test result is 0 ohms, it means that the battery is short-circuited. The short circuit rate is obtained by dividing the number of short circuits tested by the total number of tests (100,000 batteries), and the results are recorded in Table 2.

[0225] (2) Cycle test

[0226] The batteries prepared in the embodiments and comparative examples were subjected to cycle tests, and the specific test method is as follows: the batteries were subjected to charge and discharge cycle tests at a charge rate of 1.5C, a discharge rate of 0.7C, and a voltage window of 3.0V-4.5V (using a blue electric test device) for 800 cycles, and the capacity retention rate was calculated using the first discharge capacity C1 and the 800th cycle discharge capacity C800: C800 / C1×100%; the thickness T1 of the battery charged to 3.9V for the first time (tested using a PPG test device) and the thickness T2 of the battery charged to 4.5V when cycled for 800 cycles were used to calculate the thickness expansion rate (T2 / T1-1)×100%, and the cycle capacity retention rate and thickness expansion rate are recorded in Table 2.

[0227] (3) Lithium deposition test

[0228] The batteries prepared in the examples and comparative examples were subjected to a lithium deposition test. The specific test method is as follows: the batteries were cycled for 800 cycles according to the charge and discharge method in test (2), and then the batteries were disassembled to observe the lithium deposition in the area where the insulating layer on the negative electrode sheet corresponding to the positive electrode sheet covers the positive electrode active layer. The results are recorded in Table 2, where the lithium deposition conditions are ranked from light to heavy: no lithium deposition, slight lithium deposition, lithium deposition, and severe lithium deposition.

[0229] (4) Energy density

[0230] The batteries prepared in the examples and comparative examples were subjected to energy density tests, and the specific test steps were as follows:

[0231] Charge at 0.7C to the upper voltage limit (4.3V), cut-off current 0.025C, discharge at 0.5C to the lower voltage limit (2.5V), output discharge capacity, use CCD instrument to measure the length and width of the battery, use PPG instrument to measure the thickness of the battery, calculate the energy density by the formula: Energy density = capacity × operating voltage / (length × width × thickness), and record the results in Table 2

[0232] Table 2

[0233]

[0234]

[0235] It can be seen from Table 2 that the battery of the present invention has lower short circuit rate and expansion rate, higher cycle capacity retention rate, and improves the lithium plating problem of the battery while ensuring higher energy density compared with the comparative example. Since the battery of comparative example 1 does not use silicon-based materials, the short circuit rate, cycle capacity retention rate and thickness expansion rate are better, but the energy density is lower.

[0236] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A lithium ion secondary battery, characterized in that: It includes a positive electrode sheet, a separator and a negative electrode sheet which are stacked and wound; Along the winding direction of the lithium-ion secondary battery, the current collector of the positive electrode sheet has a positive electrode active layer and an insulating layer; the insulating layer partially covers the positive electrode active layer and partially covers the current collector; the insulating layer includes first inorganic particles, and the Mohs hardness of the first inorganic particles is H1, and H1 is 5-8; The negative electrode sheet comprises a negative electrode active layer, the negative electrode active layer comprises silicon-based particles, the mass content of silicon in the negative electrode active layer is c1, c1 is 4%-45%, and the Mohs hardness of the silicon-based particles is H2, H2 is 8-10; H1, H2 and c1 satisfy: 0.01≤H2×c1 / H1≤0.

7.

2. The lithium ion secondary battery according to claim 1, wherein 0.15≤H2×c1 / H1≤0.3; preferably, 0.16≤H2×c1 / H1≤0.25; And / or, c1 is 8%-25%.

3. The lithium ion secondary battery according to claim 1 or 2, wherein: The negative electrode active layer also includes carbon-based particles; Preferably, the carbon-based particles have a Mohs hardness of H3, where H3 is 1-3; Preferably, H2, the Mohs hardness H3 and c1 of the carbon-based particles satisfy: 0.02≤H2×c1 / H3≤4.5; more preferably, 0.5≤H2×c1 / H3≤1.

2.

4. The lithium ion secondary battery according to claim 1 or 2, wherein: The separator is located between the positive electrode sheet and the negative electrode sheet; Along the winding direction, the separator includes a first part and a second part, and the area where the separator contacts the insulating layer is located in the first part; the adhesion between the separator and the negative electrode sheet located in the first part is 10N / m-20N / m; And / or, the area where the separator contacts the positive electrode active layer is located in the second portion, and the adhesion between the separator and the negative electrode sheet located in the second portion is 6 N / m-15 N / m.

5. The lithium ion secondary battery according to claim 1 or 2, wherein: After 10 cycles of the lithium-ion secondary battery at a voltage of 4.55 V or less, the elongation of the current collector of the positive electrode sheet in the first direction is ≤1.5%, preferably 0.02%-0.8%.

6. The lithium ion secondary battery according to claim 1 or 2, wherein: The median particle size of the first inorganic particles is a first Dv50; The separator includes a substrate layer and a ceramic layer located on at least one side of the substrate layer, wherein the ceramic layer at least faces the positive electrode sheet; the ceramic layer includes second inorganic particles, and the median particle size of the second inorganic particles is a second Dv50; The second Dv50 / the first Dv50 is 0.25-10, and the second Dv50≠the first Dv50; preferably, the second Dv50 / the first Dv50 is 0.25-3; And / or, the first Dv50 is 0.2 μm-5 μm; preferably 0.5 μm-2 μm; And / or, the second Dv50 is 0.2 μm-5 μm; preferably 0.5 μm-2 μm.

7. The lithium ion secondary battery according to claim 1 or 2, wherein: The thickness of the positive electrode active layer is 30 μm-75 μm; And / or, the thickness of the insulating layer is 1 μm-15 μm.

8. The lithium ion secondary battery according to claim 1 or 2, wherein: In the winding direction, the size of the insulating layer portion covering the positive electrode active layer is d1, and the size of the insulating layer portion covering the current collector is d2, and d1 and d2 satisfy: d2 / d1 is 0.6-10; preferably 0.85-5; and / or, d1 is 2 mm to 15 mm; And / or, d2 is 4mm-30mm.

9. The lithium ion secondary battery according to claim 1 or 2, wherein: The insulating layer covering the positive electrode active layer is partially embedded in the positive electrode active layer; Preferably, the first inorganic particles are embedded in the positive electrode active layer.

10. The lithium ion secondary battery according to claim 9, wherein The vertical distance from the first inorganic particles in the insulating layer covering the positive electrode active layer to the surface of the insulating layer is 2 μm-15 μm, preferably 3 μm-8 μm.

11. The lithium ion secondary battery according to claim 1 or 2, wherein: The insulating layer is located at the winding head end and / or the winding tail end of the positive electrode sheet; And / or, the positive electrode sheet, the separator and the negative electrode sheet are stacked and wound to form a winding core, and the insulating layer is located at the winding head end and / or the winding tail end of the winding core; and / or, the positive electrode sheet includes a positive electrode active material, and the positive electrode active material includes a substance with the chemical formula Li a Ni b Co c Mn d M e O2, where 0.8 ≤ a ≤ 1.3, 0.8 ≤ b ≤ 0.98, 0.01 ≤ c ≤ 0.2, 0.005 ≤ d ≤ 0.14, 0 < e ≤ 0.08, and M includes at least one of Al, Zr, B, Y, Sr, W, Ti, Mg, La, Fe, and Nb.